A novel histological grading scheme for placental malaria applied in areas of high and low malaria transmission. - Muehlenbachs, A; Fried, M; Mcgready, R; Harrington, W; Mutabingwa, T; Nosten, F; Duffy, P (2010)
BACKGROUND: Plasmodium falciparum-infected erythrocytes sequester in the placenta and elicit an inflammatory response that is harmful to both fetus and mother. Histologic measurements during placental malaria might provide surrogate end points for interventional trials, but existing histologic schemes capture limited complexity and are not consistently used among study sites. METHODS: Using frozen-section histologic evaluation in Tanzania (high-transmission area), we established a novel grading scheme to separately quantify inflammation and pigment deposition during placental malaria (n = 102). To generalize this method, formalin-fixed, paraffin-embedded placental samples from Karen women in Thailand (low-transmission area) were selected from among women with documented antenatal parasitemia who were near term (n = 18). RESULTS: In the Tanzanian cohort, the inflammation and pigment-deposition scores were independently associated with birth weight, and the inflammation score was associated with chemokine levels. In the smaller cohort from Thailand, both inflammation and pigment scores were associated with birth weight, and the pigment score had an inverse trend with the number of antenatal clinic visits. CONCLUSIONS: This semiquantitative pathological grading scheme is simple to implement and captures information that is associated with outcomes in Asia and Africa; therefore, it should facilitate the comparison and standardization of results among clinical trials across areas of differing endemicity.